2011
DOI: 10.1038/clpt.2011.189
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of Interferon-Stimulated Genes and IL-28B as Host Prognostic Factors of Response to Combination Treatment for Chronic Hepatitis C

Abstract: Chronic hepatitis C (CHC) is a worldwide health problem that is highly related to liver fibrosis, cirrhosis, and hepatocellular carcinoma. The achievement of response to the current standard of care-pegylated interferon plus ribavirin-has recently been described to be associated with single-nucleotide polymorphisms (SNPs) near the IL-28B gene. Additionally, baseline expression levels of genes involved in interferon (IFN)-stimulated genes (ISGs) have been found to be related to treatment outcome. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Other study by our group has described the influence of KIR genes on the progression of chronic HCV infection and treatment outcome [29]. As well as KIR receptors, other genetic markers related to immune response have been reported [42]. One such marker is PDCD1 , which allowed us to develop a model for predicting the response to conventional therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other study by our group has described the influence of KIR genes on the progression of chronic HCV infection and treatment outcome [29]. As well as KIR receptors, other genetic markers related to immune response have been reported [42]. One such marker is PDCD1 , which allowed us to develop a model for predicting the response to conventional therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described several biomarkers of treatment response in addition to IFNL3 polymorphisms [41], [42]. Other study by our group has described the influence of KIR genes on the progression of chronic HCV infection and treatment outcome [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, no evidence was found to support that variants on IFIT1 facilitated gene splicing or gene expression. A recent research showed that a variant known as rs304478, which located within 2 kb upstream of IFIT1 , was an independent predictive factor for pegylated-IFN therapy in HCV patients[44]. Although rs304478 was not included in the present study due to its relative lower MAF in Chinese population, it highlighted a fact that IFIT1 could be potential biomarker for IFNα treatment efficiency.…”
Section: Discussionmentioning
confidence: 87%
“…The allele OASL rs12819210 constitutes an important independent factor that is significantly associated with SVR in peg-IFN-plus-ribavirin treatment, notably improving the predictive value of IL-28B rs12979860. In addition to OASL and IL-28B, the IFIT1 rs304478 A/A genotype favors a better therapy outcome, especially in patients with HCV-1 [136]. …”
Section: Polymorphisms In Host Response Genesmentioning
confidence: 99%